Pengaruh Kuliah Online terhadap Semangat Belajar Mahasiswa di Masa Pandemi Covid-19 - Mochamad Farhan Firdaus Iskandar; Thia Muthia Umar (UNISBA Press, 2022)
Abstract. The Covid-19 pandemic has changed people's lives, not only in Indonesia but also throughout the world. The outbreak of the Covid-19 virus has an impact on teaching and learning activities for students and lecturers. Activities that are usually carried out in classrooms on campus have now changed to learning at home. This condition is certainly not easy for students to pass. As for the anxiety of students because lecturers give more assignments to replace activities that are usually carried out on campus. One way to carry out learning between students and lecturers is to change the learning system by using an online or online learning system. Online learning is carried out using their respective special devices in the form of smartphones, laptops, computers, or tablets. The implementation of online learning is the right strategy in replacing learning in the classroom. This study uses the theory of instructional communication which means learning. In the era of the Covid-19 Pandemic, communication in learning is required to use online by utilizing information technology as a learning medium. Communication is done because there are goals to be achieved. One form of learning model that is facilitated and supported by the use of information and communication technology. Online learning has the characteristics of interactivity, independence, accessibility, and enrichment. Online learning can also be defined as a form of information technology that is applied in the field of education in the form of a virtual world. Online learning is essentially a learning that uses the use of information and communication technology. Abstrak. Pandemi Covid-19 telah merubah kehidupan masyarakat, tidak hanya negara Indonesia namun juga seluruh dunia. Wabah virus Covid-19 berdampak pada kegiatan belajar mengajar mahasiswa dan dosen. Kegiatan yang biasa dilaksanakan di dalam ruang kelas pada lingkungan kampus kini berubah menjadi dengan belajar di dalam rumah. Kondisi ini tentu tidak mudah dilalui oleh mahasiswa. Adapun kecemasan pada mahasiswa karena dosen lebih banyak memberikan tugas untuk menggantikan aktivitas yang biasa dilakukan dalam kampus. Salah satu cara dalam melaksanakan pembelajaran antara mahasiswa dan dosen dengan mengubah sistem pembelajaran yakni menggunakan sistem pembelajaran online atau daring. Pembelajaran online dilakukan menggunakan perangkat khusus masing-masing baik berupa smartphone, laptop, komputer, atau tablet. Pelaksanaan pembelajaran online merupakan strategi yang tepat dalam menggantikan pembelajaran di kelas. Penelitian ini menggunakan teori komunikasi instruksional yang berarti pembelajaran. Di era Pandemi Covid-19 komunikasi dalam pembelajaran dituntut untuk menggunakan daring dengan cara memanfaatkan teknologi informasi sebagai media pembelajaran. Komunikasi dilakukan karena ada maksud tujuan yang hendak dicapai. Salah satu bentuk model pembelajaran yang difasilitasi dan didukung pemanfaatan teknologi informasi dan komunikasi. Pembelajaran online mempunyai karakteristik yaitu interaktivitas, kemandirian, aksesibilitas, dan pengayaan. Pembelajaran online juga dapat didefinisikan sebagai sebuah bentuk teknologi informasi yang diterapkan dibidang pendidikan dalam bentuk dunia maya. Pembelajaran online pada hakekatnya merupakan suatu pembelajaran yang menggunakan pemanfaatan teknologi informasi dan komunikasi.